Rancang Bangun Jaringan VoIP Di PT.Jaya Muda Pertama Pekanbaru Riau (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Voice Over Internet Protocol (VoIP) is a communication that uses Internet Protocol (IP), where VoIP works to convert analog voice to digital which is sent over the internet network, VoIP functions as a medium for voice telephone conversations that utilize the internet network. The company PT.JayaMudaPertamaPekanbaru Riau makes calls using conventional telephones so that telephone costs increase, communication using VoIP is a solution for the low cost of operating from these problems, where to build a VoIP network an asterisk server is needed. Asterisk is an IP PBX software to create a communication system over the internet, asterisk functions as a VoIP network server operating system to manage gateways between VoIP and PSTN. In designing a VoIP network, it is necessary to know the quality of the network where to measure the quality of the network using the Quality Of Service (QoS) parameter, QoS is a method of measuring how good the network service quality is, the parameter used is Delay. In this study, the average delay of five clients for five days starting from the first test was 9361.6ms, the second was 9348.6ms, the third was 8780.6ms, the fourth was 9130.2ms, the fifth was 10954.2ms, the average delay obtained was very good according to TIPHON standard. The TIPHON standard serves to determine the qualification of values in internet network measurements.Keyword:VoIP, Parameter QoS, Asterisk, Standart TIPHONE, Delay